Synopsis of spine surgery - An, Howard S.; Singh, Kern (Thieme, 2016)
"The third edition of this concise, essential spine handbook expands on the previous edition, reflecting recent advances in the field. Written by highly renowned spine surgeons, the new edition is presented in full color with the addition of several hundred exquisitely crafted illustrations. Portable but comprehensive, this book offers a well-rounded perspective on surgical and nonsurgical management of spine-related conditions and disease in adult and pediatric patients. In the opening chapters, a solid clinical foundation is laid--covering anatomy, physical examination, imaging and diagnostic testing, biomechanics of the spine, and instrumentation."